2003
DOI: 10.1063/1.1563303
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation-induced photostimulated luminescence in CsBr:Eu2+

Abstract: This article concerns the unusual storage mechanism in the x-ray storage phosphor CsBr:Eu2+. Data are presented and discussed regarding the identification of x-ray diffraction patterns and the photostimulated luminescence (PSL) intensity as a function of the annealing temperature for various Eu concentrations of CsBr:Eu2+ powder crystals and the spatial correlation of trapped electrons and holes. These results together with an analysis of previous literature data enable us to propose a model explaining the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 9 publications
8
40
0
Order By: Relevance
“…Furthermore, postannealing treatments of the plates at 170-180°C in wet air increase both the sensitivity and the AA-EPR intensity of the NIP. 6,26,27 Identification of the stabilizing impurity near Eu 2+ as H 2 O or a related molecular ion, e.g., OH − , thus seems plausible. Our aforementioned ENDOR results seem to affirm this possibility.…”
Section: B Eu 2+ -Nv Cs + Modelsmentioning
confidence: 99%
“…Furthermore, postannealing treatments of the plates at 170-180°C in wet air increase both the sensitivity and the AA-EPR intensity of the NIP. 6,26,27 Identification of the stabilizing impurity near Eu 2+ as H 2 O or a related molecular ion, e.g., OH − , thus seems plausible. Our aforementioned ENDOR results seem to affirm this possibility.…”
Section: B Eu 2+ -Nv Cs + Modelsmentioning
confidence: 99%
“…Therefore, the impact of possible secondary phases can be excluded. 21,22 Collectively, the data support that similar to undoped KCl, V k centers can serve as hole-storage centers in KCl:Eu 2+ at room temperature; thus could be responsible for the fading due to increased mobility at room temperature. Moreover, the V k centers' temperature-dependent mobility (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Hackenschmied et al [4] reported a thermally activated increase in PSL yield in CsBr:Eu 2+ . This increase was reported to be related to the formation of new Eu 2+ -precipitations in the CsBr matrix such as CsEuBr 3 and Cs 4 EuBr 6 observed after an annealing process [5].…”
Section: Introductionmentioning
confidence: 84%